2022
DOI: 10.3390/coatings12081099
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Implant Prosthesis Treatment Planning and Execution Following Bone Repair Procedures Using Dynamic Surgical Navigation in Augmented Areas

Abstract: Successful implant placement in augmented sites depends on the appropriate bone volume and quality, as well as careful planning of the procedure. Minimizing risks during the surgical and healing phases is also of great importance. A very promising technique has been introduced, which partially meets the above criteria. This technique is designed to increase the precision and reduce the invasiveness associated with surgical procedures during implantation. The aim of this clinical study was to analyze the accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Furthermore, on the basis of a comparative analysis of the planning and execution of freehand implant treatment using navigation, it has been shown that dynamic navigation may improve the quality and safety of surgical procedures and reduce the risk of complications compared to freehand implant placement [48].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, on the basis of a comparative analysis of the planning and execution of freehand implant treatment using navigation, it has been shown that dynamic navigation may improve the quality and safety of surgical procedures and reduce the risk of complications compared to freehand implant placement [48].…”
Section: Discussionmentioning
confidence: 99%
“…The quality and quantity of available bone are assessed through diagnostic tools such as X-rays and CT scans [10,11]. The appropriate type, size, and positioning of the implant are decided based on the treatment planning [12]. Local anesthesia is typically administered to numb the area where the implant will be placed.…”
Section: Introductionmentioning
confidence: 99%